Jack and the beanstalk: hello friend (Hello friend India, 2010)
Jack trades his cow for magical beans that grow into a giant beanstalk reaching the sky. He climbs up and encounters a giant and treasures like a golden goose. After several adventures, Jack defeats the giant and brings prosperity to his home.